Prospects for Archeology in Jordan & Syria - Sauer, James A. (The Biblical archaeologist, 1982)
Jordan and Syria, which together comprise a very large percentage of the area of Syria-Palestine, have rich archeological histories which include the Paleolithic-Neolithic periods, the Bronze-Iron Ages, the Classical periods, and the Islamic periods. Many countries are participating in the recovery of this history, and the new evidence that is coming from this research is of great significance for many problems of Syro-Palestinian archeology.